Output-Based Aid and Sustainable Sanitation - World Bank (Washington, DC, 2012)
Global Partnership on Output-Based Aid (GPOBA), in association with the Water and Sanitation Program (WSP), initiated a study to examine whether OBA has the potential to improve the delivery of public financing to the sanitation sector and improve access to sustainable sanitation services. The first phase of the study consisted of reviewing experience to date with OBA for sanitation and examining the potential for its application. Phase one led to the publication of a GPOBA working paper. During phase two, concept notes are being prepared to identify how OBA approaches could be introduced in a number of sanitation projects or programs that are either ongoing or in the process of being designed. Key questions raised in the study included: What explains such limited use of OBA-financing approaches for sanitation? How can OBA subsidies be delivered to providers of sanitation services? What other components (e.g., support services to small-scale independent providers, micro-finance, etc.) may be required to improve chances of success of OBA schemes for sanitation?